PENGARUH JANGKA PENDEK JOB INSECURITY DAN KOMPENSASI TERHADAP KEPUASAN KERJA KARYAWAN OUTSOURCING DI PT. ASKES (PERSERO) KANTOR PUSAT - Elven Martini; Lieke E.M. Waluyo (Jurnal Psikologi, 2014)
The aim of this study is to measure the contribution of job insecurity and compensation to work satisfaction in outsourcing employee at PT Askes (Persero) main office. This is a quantitative research using multiple regression for the data analysis. This research has 164 participants consist of teachers, security officers, cleaning service officers, meeting maids and drivers. The result shows that job insecurity and compensation have contribution to work satisfaction as much as 42.1%. Based on categorization, participant’s work satisfaction and job insecurity are in the moderate level, but the compensation is in the high level.Keywords:  Job insecurity, Compensation, Work satisfaction